Tourism Influence on The Economy: Analysis of The Study of The Origin of Foreign Tourist Visits - Ksamawan, Kdwi wahyu (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2019)
The influence of foreign tourist arrivals based on the region of origin on economic growth was analyzed in this study, using GDP data as a proxy for economic growth, the number of tourist visits, the Consumer Price Index, and the monthly period of exchange for 2007-2016. This study uses secondary data with the Error Correction Model (ECM) regression method with short and long-term calculations. The results showed that the variable number of tourist visits had an effect on GDP in the continents of Asia, Europe, Middle-East, and Oceania while in the long run in all continents except America. The exchange rate variable in the short term has a negative effect on GDP in the American Continent and the Middle East, while in the long run, the exchange rate variable has a positive effect on GDP in the Asean continent and Europe. The CPI variable only has a positive effect on GDP in the long run for all continents except America. So that it can be concluded that not all continents have a positive impact on GDP, one of which is the American continent, so in order to optimize and increase economic growth, it should be stressed that the cost of developing the tourism sector in America should be allocated more proportionally or diverted to continents of Asia, ASEAN, Oceania, Europe and the Middle East.of developing the tourism sector in America should be allocated more proportionally or diverted to continents of Asia, ASEAN, Oceania, Europe and the Middle East. Keywords: Error Correction Model,GDP, Tourism JEL: R10; Z3